A case of Philadelphia chromosome‐positive acute lymphocytic leukaemia with type I CD36 deficiency. Issue 1 (14th June 2021) - Matsui, Marina; Kajiwara, Koichi; Tsukada, Masao; Iwama, Kanichi; Yamada, Kazunari; Kodo, Hideki; Seto, Katsuya; Tonami, Kaoru; Ando, Moe; Matsuhashi, Mika; Watanabe‐Okochi, Naoko; Tsuno, Nelson Hirokazu; et al.
Abstract: Background: CD36 is a glycoprotein expressed on platelets and monocytes of the blood. There are two types of CD36 deficiency, type I and type II. Individuals with type I‐deficiency do not express CD36 in any cell type and can produce the CD36 antibody, which causes pathological conditions, such as fetal/neonatal alloimmune thrombocytopenia (FNAIT) and platelet transfusion refractory (PTR), through antigenic exposure via transfusion or pregnancy. Case presentation: We experienced a case of Philadelphia‐positive acute lymphoblastic leukaemia with PTR. In addition to the CD36 antibody, multiple‐specificity HLA antibodies were present in the patient's plasma, requiring transfusion of HLA‐compatible and CD36‐negative platelets (PC‐HLA). Since the number of donors was limited, it was necessary to set‐up a blood transfusion schedule so that hyper‐fractionated cyclophosphamide, vincristine and doxorubicin therapy (hyper‐CVAD) and ponatinib combination chemotherapy could be safely administered to achieve molecular remission. Rituximab administration resulted in reduced levels of both CD36 antibody and HLA antibody. Given the expression of CD36 on haematopoietic stem cells and the limited availability of CD36‐negative PC‐HLA, haematopoietic stem cell transplantation (HSCT) was not considered to be an option. Conclusion: If CD36‐negative, allogeneic haematopoietic stem cell donors are unable to be found, the indications for HSCT in patients with type I CD36‐deficiency should be carefully weighed. In the present case, molecular remission has been able to be maintained to the present day after completion of a two‐year maintenance regimen.